Evaluation of the Efficiency of the Plant Urtica dioica L. in Controlling Some Stages of the Greater Wax Moth (Lepidoptera: Pyralidae) Galleria mellonella L. (NTU Journal of Agriculture and Veterinary Science, 2025)
The results of the study showed the superiority of both the alcoholic and aqueous extracts in recording the highest egg mortality rates at the third and fourth concentrations (100.00 and 93.33%, respectively), while the dry powder recorded (26.67 and 36.67%). As for the mortality of third and fifth instar larvae, the alcoholic extract at the third concentration after 96 hours of treatment, and at the fourth concentration after 72 and 96 hours, recorded a mortality rate of (100.00%). Regarding the mortality rates of the fifth instar, all treatments showed gradually increasing mortality rates, especially the alcoholic extract at the fourth concentration after 96 hours, which gave the highest mortality rate (96.67%). The aqueous extract and dry powder at the final concentration recorded (86.67 and 66.67%, respectively). The pupal mortality rate with the alcoholic extract was (80.00%), while the third concentration of the same treatment recorded (73.33%), which did not differ significantly from the aqueous extract treatment at both the third and fourth concentrations (73.33%). The lowest pupal mortality rate was recorded with the dry powder (26.67%).